UPAYA PELESTARIAN BAHASA JAWA MELALUI MEDIA PEMBELAJARAN BERBASIS AUDIOVISUAL DI MADRASAH IBTIDAIYAH - Taqiyah, Barirotut; Farikha Rosyidah, Siti; Khamidah, Amalia; Mujiburrohman, M; Abdun Nasir, M. Fikri (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This article discusses efforts to preserve the Javanese language through audiovisual-based learning media in Islamic elementary schools. As we know, today's children are starting to pay no attention to the Javanese language. With the development of an advanced era, the Javanese language is often eroded by the influence of today's progress. The purpose of this research is to make young people and teachers aware of the importance of an effort to preserve culture starting from an early age. Hopefully, this advanced era can be utilized in preserving the Javanese language through audiovisual media. The use of this audiovisual will be easier because nowadays many people have technological devices. This research is a qualitative research using literature review techniques, collecting relevant data. Then analyze and reduce the results of the research. Describes a literature study on efforts to preserve the Javanese language through audiovisual media at Madrasah Ibtidaiyah